Experimental Study of Updraft Gasification of Rice Husk and Coal to Produce Syngas - Nugroho, Fiqrei Akbar; Syarief, Akhmad; Mikhael, Allexyus; Supit, Geovani Glen (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Limited resource of fossil fuel inspires many research activities to search for alternative energy. This work offers alternative solution to address this problem through charcoal gasification. The goal of this research is to find the amount of syngas produced in the gasification is process. The alternative fuel was produced from the mixing rice husk and low quality coal due to their abundant resource in South Kalimantan. The mixture was then gasified at 500 Â°C. The highest syngas volume at 29.56 L was in the sample of SP 200 gr and BB 0 then followed at 25.7 L for ratio SP 180 gr : BB 20 gr. The lowest produced syngas 19.45 was produced from the sample with ratio SP 100 gr : BB 100 gr. This gasification process also resulted in side product, i.e. tar component which varies from 22.5 mL to 58.75 mL.